The Nun's story - Anderson, Robert; Blanke, Henry; Zinnemann, Fred (Warner Home Video, 1974)
Traces the story of Sister Luke, who enters the convent as a young girl, serves on the staff of a mental hospital and in a Belgian Congo, and eventually leaves the convent.